2022
DOI: 10.29219/fnr.v66.8714
|View full text |Cite
|
Sign up to set email alerts
|

Arborinine from Glycosmis parva leaf extract inhibits clear-cell renal cell carcinoma by inhibiting KDM1A/UBE2O signaling

Abstract: Background: Arborinine is a natural product isolated from Globigerina parva (G. parva) leaf extract that shows strong anticancer activity with its role in clear-cell renal cell carcinoma (ccRCC) unreported. Objective: We aim to evaluate the role of Arborinine in ccRCC. Design: Arborinine was tested for its effects in ccRCC cell lines in vitro and in silico. Results: Arborinine conferred inhibitory effect to ccRCC cells at reasonable doses. Arborinine showed inhibitory effects on Lysine Demeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Upon further validation, these targets can lead to new treatment options for aggressive breast cancer subtypes such as Triple negative breast cancer. Similarly, many identified genes, such as KDM1A in astrocytoma, MMP3 (Bufu, et al, 2018) in glioblastoma, and PSEN1 in oligodendroglioma, have previously been correlated with cancer (Feng, et al, 2022; Xu, et al, 2018; Zhang, et al, 2022). These 3 genes also have inhibitors available, such as ladademstat, which can potentially target KDM1A (LSD1) (Salamero, et al, 2020), thus can be used to inhibit the growth of astrocytoma glioma.…”
Section: Discussionmentioning
confidence: 94%
“…Upon further validation, these targets can lead to new treatment options for aggressive breast cancer subtypes such as Triple negative breast cancer. Similarly, many identified genes, such as KDM1A in astrocytoma, MMP3 (Bufu, et al, 2018) in glioblastoma, and PSEN1 in oligodendroglioma, have previously been correlated with cancer (Feng, et al, 2022; Xu, et al, 2018; Zhang, et al, 2022). These 3 genes also have inhibitors available, such as ladademstat, which can potentially target KDM1A (LSD1) (Salamero, et al, 2020), thus can be used to inhibit the growth of astrocytoma glioma.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it was demonstrated that arborinine can block LSD1/KDM1A activity in clear-cell renal cell carcinoma ccRCC cell lines, sensitive or resistant to the kinase inhibitor sorafenib. In this case again, the compound blocked cell migration and invasion, cell cycle progression, and induced apoptosis [ 62 ]. A molecular modeling analysis suggested that arborinine could bind directly to the active site of LSD1, and blocks downstream signaling activities, notably the expression of the ubiquitin-conjugating enzyme E2O (UBE2O), an important protein for cancer cell survival and proliferation [ 62 ].…”
Section: Bioactive Phytochemicals From R Angustifolia ...mentioning
confidence: 99%
“…In this case again, the compound blocked cell migration and invasion, cell cycle progression, and induced apoptosis [ 62 ]. A molecular modeling analysis suggested that arborinine could bind directly to the active site of LSD1, and blocks downstream signaling activities, notably the expression of the ubiquitin-conjugating enzyme E2O (UBE2O), an important protein for cancer cell survival and proliferation [ 62 ]. The observation that arborinine represses LSD1/UBE2O signaling in ccRCC opens novel perspectives for research.…”
Section: Bioactive Phytochemicals From R Angustifolia ...mentioning
confidence: 99%